Neo-Kantian roots in Stanisław Brzozowski’s philosophy. Review of the problem of regularity - Witkowska, Natalia (Folia Philosophica, 2018)
The article focuses on the presentation of Kantian sources in Stanisław Brzozowski’s philosophy, who was an outstanding philosopher, writer, and critic. Due to the value of his work, appreciated for over a hundred years by both domestic and foreign researchers, in the article, I emphasize the issue related to the proper conduct of the analysis of its activities. I also point out the most frequent errors that lead to interpretative contradictions within the philosophical reflection that Stanisław Brzozowski created.